UPIN AND IPIN FILM TRANSLATION ERRORS (MALAYSIA LANGUAGE TO INDONESIA LANGUAGE) - Andestend Andestend (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract:The focus of this study is the translation errors contained in the subtitle film Upin and Ipin Terlajak Laris part one (Malaysian language into Indonesian. The research method uses a qualitative approach. Data sources are in the form of documents (translation results). Data collection techniques use document analysis. Data analysis techniques 1. Transcribe the conversations in the movie Upin and Ipin, 2. Group the languages of Malaysia and Indonesian 3. Analyze the incompatibility between Malay and Indonesian languages, 4. Conclude the results of the analysis. The results are 20 words that are not accurate in translation.